Factors influencing the perception of shunt devices in children after ventriculo-peritoneal shunts - Lijun Wan; Kuo Zeng; Zhongyin Guo; Wang Xiang; Minhai Dong; Zirong Chen; Xiaolin Zhang; Feng Wan (BMC Neurology)
Abstract Objective The impact of hydrocephalus on the emotional, cognitive, and social health of children is frequently overlooked when measuring clinical outcomes in children with hydrocephalus. The aim of this study was to determine factors that influence the subjective perception of the subcutaneous shunt devices in children with hydrocephalus after ventriculo-peritoneal shunts (VPS). Methods A retrospective analysis was performed on a cohort of 86 pediatric patients who underwent VPS at the Department of Neurosurgery, Tongji Hospital, between January 2012 and July 2022. Clinical information such as gender, age at surgery, age at follow-up, post-shunt complications, postoperative shunt replacements or shunt revisions, adjustments for valve opening pressure(VOP), brands of shunt devices, family situation, and the patients’ subjective perception of the subcutaneous shunt devices were collected by telephone follow-up. Results Of the 86 children, 63 (73%) perceived the existence of the subcutaneous shunt devices (32% at the level behind the ear, 16% at the chest, 52% at the neck), among which 3 children were particularly sensitive and more anxious. The independent risk factors for the subjective perception of shunt devices were age at follow-up (≥ 7 years) and post-shunt complications with odds ratios of 3.860 (P = 0.02) and 4.956 (P = 0.02) respectively. Conclusion In pediatric hydrocephalic patients who have undergone VPS, those aged seven years or older or who experienced post-shunt complications may exhibit a significant subjective perception of subcutaneous shunt devices. It is crucial for parents to be cognizant of this potentiality, and offer attentive care and thorough explanations to relieve any associated anxieties.